Voice changes in Children with Attention Deficit Hyperactivity Disorder (ADHD) - Zienab Khalaf; Effat Ahmed Zaky; Fatma Wafik Shahin; Shaimaa Osman Abdelhamid; Marowa Abd El Wahab (International Journal of Medical Toxicology and Legal Medicine, 2024)
Attention Deficit Hyperactivity Disorder (ADHD) is a neurodevelopmental disorder characterized by symptoms of inattention, hyperactivity, and impulsivity, which can affect children’s behavior, learning, and social interactions. Dysphonia in ADHD refers to a persistent alteration in voice production often linked to vocal misuse, overuse, or other environmental and physical factors. Children with ADHD may be at an increased risk for developing voice changes due to various ADHD-related factors (e.g., impulsivity, difficulty with self-regulation, excessive talking, or hyperactivity affecting vocal folds).